Introducing Greek Alchemy to Christianity: Inclusion and Exclusion of Religious Elements in Stephanus’s Lessons - Carlotta, Vincenzo (ARYS. Antigüedad: Religiones y Sociedades, 2022)
One of the most noticeable features distinguishing Byzantine works on alchemy from the earlier Greco-Egyptian alchemical tradition is the widespread presence of Christian prayers and direct references to specifically Christian ideas and beliefs. By focusing on Stephanus’s Lessons (7th cent.), the first alchemical work including extensive references to Christianity, the paper will explore how alchemy was Christianised in the early Byzantine period. The first part of this study will analyse the strategies adopted by the author of the Lessons to frame alchemy as a Christianised discipline aiming at discovering the divine principle hidden in the natural world. In the second part, the limitations of this process of Christianisation of alchemy will be pointed out by examining if and to what extent specifically Christian ideas were included in Stephanus’ treatment of alchemy and its operations, and if the introduction of a Christianised framework into an alchemical work entailed the exclusion of previous non-Christian alchemical ideas. The results of this twofold analysis will show the complexity and inextricable tensions of the process of Christianisation undergone by the alchemical discipline when it started to be practiced in the socio-cultural context of the Byzantine world.
Keywords: Byzantine alchemy; christianisation; Neoplatonism; pagan wisdom; Stephanus